Kekerasan Seksual di Perguruan T ANALISIS PENGARUH RELASI KUASA DAN PATRIARKI DALAM FENOMENA KEKERASAN SEKSUAL DI PERGURUAN TINGGI DALAM PERSPEKTIF HAK ASASI MANUSIA : PENGARUH RELASI KUASA DAN PATRIARKI DALAM FENOMENA KEKERASAN SEKSUAL DI PERGURUAN TINGGI DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA - Refika, Fanny (UIR Law Review, 2023)
Sexual violence that occurs in the college environment has become a serious problem, the rise of sexual violence cases that occur in the university environment has again made many parties aware that there is abuse and deviation of power, where someone who has a higher position and / or power has imposed his will on others whose position and / or power is lower. The method used to answer the problems mentioned above is the Normative Legal Research method. Patriarchal culture makes a clear distinction between men and women, especially when it comes to male-dominated power. Students who are victims of sexual violence are afraid to face academicians who have “influence” or “power”, so they are forced to remain silent. Permendikbudristek Number 30 of 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education Environment highlights the influence of power relations and culture as the main causes of sexual violence cases. become a stigma inherent in social values, cultural aspects and structural factors. Sexual violence in the university environment committed by the academic community is a violation of human rights, therefore this regulation was created to provide a sense of security to women from the influence of power relations and also patriarchal culture found in the university environment. Keywords: Power Relations; Patriarchy; Sexual Violence in Higher Education